Analisis Perkembangan Kosakata Bahasa Indonesia Pada Masa Pandemi Covid-19 - Sutarini, Sutarini; Sutikno, Sutikno; Wariyati, Wariyati (TIN: Terapan Informatika Nusantara, 2021)
The Covid-19 pandemic has at least had a positive impact on the development of the Indonesian language. Many new words are used to convey information related to the Covid-19 pandemic. The vocabulary and terms used to inform about Covid-19 were originally in English. This is very reasonable because the covid-19 pandemic has not only attacked the country of Indonesia, but there are several countries that were first affected by the Covid-19 virus and have become cases of a global pandemic. The vocabulary and terms that were originally in English now have equivalent words in Indonesian, as an effort to avoid misunderstandings in receiving information related to the Covid-19 pandemic. At present, the use of foreign terms has begun to be reduced and replaced with new terms in Indonesian, although most of the Indonesian vocabulary is not yet in the KBBI. The use of the Indonesian language plays an important role in delivering information related to the spread of the Covid-19 virus among the Indonesian people. This shows that language is dynamic, that is, it can adapt to the current developments that are now very much changing in the global era by applying new Indonesian vocabulary during the Covid-19 pandemic as communicative information delivery among the Indonesian people